Hugh Broughton and the King James Bible, revisited - Macfarlane, K (Equinox Publishing, 2020)
Hugh Broughton (1549–1612) is best known today as the eccentric puritan who, having been excluded from the translation committees of the King James Bible, published a vicious attack on the final product. While this has been enough to guarantee Broughton a passing mention in most histories of the topic, there remain few systematic analyses of the complex and shifting reasons behind his strong dislike of the new translation. This article expands our understanding of Broughton’s attitude to the English Bible through the analysis of four previously unknown manuscript sources, preserved in British Library MSS Sloane 3088 and Egerton 791. After introducing the sources and giving an overview of their provenance, the article highlights some of their most remarkable features and explains their significance both for our knowledge of Hugh Broughton in particular as well as for studies of vernacular translation more broadly.